Desempenho luminoso e energético de ambientes de escritório: estudo de caso em Paranavaí - PR - Miranda, Débora Thomé (2020)
The constant search for the performances of luminous and energetic efficiencies in buildings is due mainly to the need for energy savings, since its consumption has increased significantly in the last decades. Providing good lighting in the environments requires that minimum levels of lighting be guaranteed so that it does not negatively affect the occupant's health and contributes positively to their productivity. The present study aimed to evaluate the office lighting system of an existing building from the 1990s in order to verify the luminous and energetic performances and explore new systems with the potential to improve performances. The analyzes were carried out by means of computer simulations using the DIALux evo program, which allows the evaluation of artificial and natural illuminations simultaneously. Based on the results obtained, it was found that the existing lighting system does not meet the average recommended illuminance value. Therefore, based on simulations with new arrangements and types of luminaires/lamps, two more effective systems were presented: one considering the replacement of T12 fluorescent lamps with LED luminaires, which provided an energy saving of 15.5%, and another that used artificial lighting to complement the available daylight during working hours with the aid of a dimming system linked to daylight. This last system showed an energy saving of up to 65% when compared to the existing lighting system. Regarding light quality, the limit lighting power density showed an improvement of more than 60% in the new systems. Therefore, by modifying the arrangement of the luminaires and replacing them with LEDs, the artificial lighting system reached the average illuminance value recommended by the standard and also generated a significant reduction in the consumption of lighting electricity. Electricity savings were also observed when assessing the potential for using natural light associated with the use of dimmers.